The co-movement between commodity prices and the economic growth of Malaysia - Saizal Pinjaman; Shairil Izwan Taasim; Wong Sing Yun; Jain Yassin (ResearchGate, 2024)
Research Originality: This research is an initial attempt to unveil the structure of the dynamic relationship between commodity prices and Malaysia's economic growth at various frequencies and moments in time. Research Objectives: This paper investigates the co-movement and leadlag relationship between commodity prices and the economic growth of Malaysia at different frequencies and moments in time. Research Methods: The relationship between the variables is studied using monthly data from 2015 to 2022 and the time-frequency analysis of the Continuous Wavelet Transformation model. This method analyses the direction and lead-lag relationship between two-time series to determine which variables are leading and the direction of their co-movement. Empirical Result: The relationships between commodity prices and economic growth are varied depending on frequency and moments in time. In the short run, most commodity prices exhibit an inverse relationship led by economic growth. Meanwhile, a positive comovement with economic growth is indicated for most commodity prices in the medium run. These variables mostly move in unison, except for rubber and palm oil, which led to the relationship. Nevertheless, the co-movement of commodity prices and economic growth showed a diminishing magnitude in the long run. Implications: Malaysia's policy frameworks should consider the economic dynamic responses towards commodity prices in facilitating its economic growth. In addition, efforts should be made to diversify economic activities, reducing dependence on commodities in the country's trade basket.